O Instituto Nacional de Educação de Surdos e a formação de professores para surdos em Sergipe (1959-1961) - Seixas, Catharine Prata (2015)
This study analyzes the training for teachers of deaf people in Sergipe in the years 1959 to 1961, seeking to know the pedagogical practices that guided the Specialization Course for Teachers of Deaf, sponsored by the National Institute for Deaf Education. For the production of this work, we followed the precepts of Cultural History, articulated to the concepts of memory, collective memory, writing, history and culture, in order to relate them to the researched sources: laws, class record books, minutes, curricula, textbooks, annals. Among the various bibliographic references used, we can highlight the following authors regarding the explored theoretical framework: Mazzota (2005), Jannuzi (2006), Rocha (2009), Souza (2009), Soares (1996, 2005) and Souza (2007). The aim of this study is to insert, in Sergipe educational historiography, aspects of the educational history of deaf, and specifically the history of the training for teachers of deaf people.